Virtual Classroom in the Hand: Adapting an E-Learning Platform for English Language Learners - Nur Latifah; Nikhil Joshi; Novita Kusumaning Tyas; Nining Fitriani; Ariana Oktaviana (Yayasan Adra Karima Hubbi, 2024)
Background. The development of digital technology has changed the paradigm of foreign language education, but existing e-learning platforms are still not fully able to accommodate the diversity of individual needs of students. Purpose. This study aims to develop and test the effectiveness of adaptive e-learning platforms that are able to dynamically adjust learning content based on students' characteristics, learning styles, and English language skills. Method. The results showed a significant increase in English language competence in the experimental group with an average score increase of 23.2 points. Statistical analysis revealed a positive correlation between content personalization and learning motivation (p<0.01). Adaptive platforms have been proven to be effective in lowering language anxiety and increasing students' confidence. Results. The conclusion of the study confirms the transformative potential of adaptive technology in foreign language education. A platform that integrates artificial intelligence, psychological approaches, and innovative pedagogical is able to create a personalized and meaningful learning experience. Conclusion. The study concludes that mobile-compatible e-learning platforms can effectively support ELLs, providing an engaging and accessible learning environment that enhances language proficiency. Further research is recommended to explore long-term retention rates and the impact of additional personalized features.